2013
DOI: 10.1093/treephys/tps125
|View full text |Cite
|
Sign up to set email alerts
|

Solute accumulation and elastic modulus changes in six radiata pine breeds exposed to drought

Abstract: Drought is one of the main abiotic factors that determine forest species growth, survival and productivity. For this reason, knowledge of plant drought response and the identification of physiological traits involved in stress tolerance will be of interest to breeding programs. In this work, several Pinus radiata D. Don breeds from different geographical origins were evaluated along a water stress period (4 weeks) and subsequent rewatering (1 week), showing different responses among them. Leaf water potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…accumulation of solutes in tomatoes caused a slight decrease in osmotic potential during RW treatment that was significantly correlated with sugar and proline accumulation in leaves. Indeed, sugars and proline are compatible solutes that play a role in tolerance to abiotic stress (Loutfy et al 2012;Sperdouli & Moustakas 2012;De Diego et al 2013;Liu et al 2015). Additionally, the increased level of proline and total carbohydrates during RW was dependent on the species: proline primarily accumulated in S. chilense, whereas the preferred solute in S. peruvianum was total carbohydrates (Figs 3, 8).…”
Section: Discussionmentioning
confidence: 99%
“…accumulation of solutes in tomatoes caused a slight decrease in osmotic potential during RW treatment that was significantly correlated with sugar and proline accumulation in leaves. Indeed, sugars and proline are compatible solutes that play a role in tolerance to abiotic stress (Loutfy et al 2012;Sperdouli & Moustakas 2012;De Diego et al 2013;Liu et al 2015). Additionally, the increased level of proline and total carbohydrates during RW was dependent on the species: proline primarily accumulated in S. chilense, whereas the preferred solute in S. peruvianum was total carbohydrates (Figs 3, 8).…”
Section: Discussionmentioning
confidence: 99%
“…In our preliminary studies, we demonstrated that exposure to a short drought period of four weeks induced a different osmotic response in each P. radiata breed (De Diego et al, 2013b). In addition, although all plants recovered their osmotic potential after rewatering, some solutes, especially amino acids, were maintained at high levels, including l-proline (Pro) and ␥-aminobutyric acid (GABA) as the most abundant ones.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, although all plants recovered their osmotic potential after rewatering, some solutes, especially amino acids, were maintained at high levels, including l-proline (Pro) and ␥-aminobutyric acid (GABA) as the most abundant ones. Controversially, amino acids contributed in less extent to plant osmotic adjustment, pointing out their possible role as signal molecules that activate protection mechanisms to mitigate the effects of water stress (Kinnersley and Turano, 2000;Vendruscolo et al, 2007), and suggesting their possible implication in improving tolerance against future water stress situations (De Diego et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others, such as auxins, gibberellins, and cytokinins, are also involved in stress responses via complex signaling networks (Verma et al, 2016;Verslues, 2016). Phytohormones regulate stress responses that often include increases in antioxidant capacity and accumulation of osmolytes (Cvikrová et al, 2012;De Diego et al, 2013;Hüve, Bichele, Tobias, & Niinemets, 2006;Nagao, Minami, Arakawa, Fujikawa, & Takezawa, 2005;Zhao, Shi, Liu, Jia, & Li, 2015). Furthermore, information about experienced stresses ("stress memories" or "stress imprints") can be stored in plants and may often increase their tolerance of recurrent stresses (Bruce et al, 2007;Nikiforou & Manetas, 2018).…”
Section: Introductionmentioning
confidence: 99%